DAMPAK PANDEMI COVID-19 TERHADAP KESEHATAN KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zebua, Darwin (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2025)
This research aims to examine the impact of the Covid-19 pandemic on the financial health of companies listed on the Indonesia Stock Exchange, using the Zmijewski financial distress analysis model. This research covers all sectors except the financial sector, by comparing the financial conditions of companies before and during the pandemic. The research results show that the pandemic not only had negative impacts but also positive impacts on several sectors. The decline in revenue is the main cause of companies experiencing financial distress, especially in the non-essential sector that faces operational restrictions. In addition, inefficient management practices and increased debt to cover operational costs have further worsened the company's financial condition. Conversely, several companies in certain sectors, such as energy, managed to record positive performance thanks to increased global demand and debt control. The technology sector proved to be the most stable without experiencing significant impacts, either positive or negative. These findings provide an overview of the patterns of financial distress during the pandemic and identify key factors influencing the financial performance of companies.